OPTIMALISASI POTENSI DESA MELALUI PENGOLAHAN PISANG MENJADI PRODUK UNGGULAN YANG BERNILAI EKONOMIS DI DESA KARANGREJO GUMUKMAS JEMBER - Rofiq Hidayat ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2025)
This community service initiative is motivated by the abundant banana harvests in Karangrejo Village, Gumukmas District, Jember Regency, which have not yet been optimally processed into value-added products. Data from the Jember Regency Agriculture Office (2023) indicate that the Jember region, including Gumukmas, is one of the banana production centers in East Java. However, this commodity is still predominantly sold in its raw form without downstream processing (jemberkab.go.id). The primary objective of this program is to develop local potential by processing bananas into superior economic products such as banana chips, dried banana (sale), and banana dodol, in order to improve the economic welfare of village residents. The program adopts the Asset-Based Community Development (ABCD) approach, which emphasizes community development through local potentials and strengths. Implementation involves asset mapping of the village, hands-on training in banana product processing, and entrepreneurial mentoring for women’s groups and local youth. The results demonstrate an improvement in residents’ skills in processing bananas, the establishment of two new business groups, and an increase in income among participating villagers. This program has had a positive impact on strengthening local economic independence and introducing a distinctive product branding for Karangrejo Village.